Control and optimization of cure cycle for thick-sectioned thermoset composites manufacturing - Ünlühisarcıklı, Özer. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
The objective of this study was to minimize the temperature gradients encountered in thick-sectioned thermoset composites manufacturing. For this purpose, a finite difference analysis based on mathematical models representing the curing phenomenon was developed. An optimization method, namely the sequential simplex algorithm was coupled with the analysis to minimize the temperature gradients. A PID controller was developed in LabVIEW to allow the execution of cure cycles with arbitrary temperature profiles. An experimental setup was prepared, and experiments were carried out in order to check the consistency of the analysis with the experimental results. Interpreting the experiment results, the efficiency of the approach was discussed, and potential ameliorations to the study were proposed.
Keywords: Thermosetting composites.; Manufacturing processes.